Measurements of top-quark pair differential cross-sections in the lepton plus jets channel in pp collisions at root s=13 TeV using the ATLAS detector - Onofre, A. (2017)
Measurements of differential cross-sections of top-quark pair production in fiducial phase-spaces are presented as a function of top-quark and t (t) over bar system kinematic observables in proton-proton collisions at a centre-of-mass energy of root s = 13TeV. The data set corresponds to an integrated luminosity of 3.2 fb(-1), recorded in 2015 with the ATLAS detector at the CERN Large Hadron Collider. Events with exactly one electron or muon and at least two jets in the final state are used for the measurement. Two separate selections are applied that each focus on different top-quark momentum regions, referred to as resolved and boosted topologies of the t (t) over bar final state. The measured spectra are corrected for detector effects and are compared to several Monte Carlo simulations by means of calculated chi(2) and p-values.